Extraction of People’s Perception Toward Horseshoe Crab Existence in Northeast Coast of India - Pati, Siddhartha; Shahimi, Salwa; Edinur, Hisham Atan; Nelson, Bryan Raveen; Acharya, Diptikanta; Dash, Bisnu Prasad (Frontiers in Marine Science, 2020)
Understanding local community attitudes toward wildlife and their environment is critical for making sensitive conservation planning and management decisions particularly for conservation-neglected species like Tachypleus gigas. A questionnaire-based interview was carried out on 388 local households from 12 different villages in Balasore, Odisha, between September 2018 and February 2019, which uses a theoretical mapping on attitudes toward horseshoe crabs. We found that 53% of interviewees accepted the presence of horseshoe crabs in their area, 27% have oppressive attitudes, and the remaining 20% were having mixed feelings. Most respondents (>60%) considered horseshoe crabs to bring tangible benefits such as esthetic, monetary, and cultural significance. However, a handful of respondents expressed oppressive attitudes because horseshoe crabs damage their fishing nets (<20%). Both principal component and stepwise analyses revealed that age, gender, and education were demographic components that closely relate local community perceptions toward the conservation-neglected horseshoe crabs that remain threatened by by-catch. We encourage socioeconomic monitoring particularly during rapid economic and infrastructure development to minimize knowledge erosion and to appreciate local ecological knowledge for better conservation management in India.